EFFECTS OF THE FISCAL PACKAGE FOR 2009 IN THE BUDGETARY INCOMS INTO THE REPUBLIC OF KOSOVO - Imeri, Vehbi (European Scientific Journal, ESJ, 2012)
In this study paper has been discussed the analyze of modification effects of the fiscal package done in 2009 by the Government of the Republic of Kosovo and the Ministry of Finance as well as the effects of these modifications in realization of the budgetary revenues as regards to the periods of fiscal years 2007, 2008 and 2009. In the analyses are included direct and indirect revenues, realized in 2009 because in the 2009 have been made modifications in tax ratings and their effects in budgetary revenues as well as the comparison of each tax rate. In particular in this study paper has been analyzed effects of these modifications. Adoption of the fiscal package which entered into force on 01.01.2009 contains modifications of the tax rates as follows: 1. Value Added Tax from 01.01.2009 is increased the tax rate from 15% which was in the period of time from 01.07.2001 until 31.12.2008 in the tax rate of 16 %, 2. Tax ratio in the incomes of the corporate is decreased from 20% which was from 01.01.2005 until 31.12.2008 in the percentage of 10%, 3. The tax rate in personal income tax were decreased from 5 %; 10 % and 20 % which were in the period of time from 01.01.2005 until 31.12.2008 in 4 %; 8% and 10% , 4. The Tax Rate in Interest, dividend, gambling games and rent were decreased from 16% & 20% into 9% & 10%. Therefore in this study paper shall be analyzed if there was any effect in increase or decrease of the budgetary incomes by modifications made in the fiscal package.